Prevalence and Impact of Tobacco Consumption Among the students in Kathmandu Valley - Thapa, Anil (Journal of Advanced Academic Research, 2025)
This study examines the prevalence and determinants of tobacco use among adolescent students in the Kathmandu Valley, where tobacco consumption remains a substantial public health concern. Using a mixed-method design, data were collected from a purposive sample of 250 students aged 13–19 years from grades 8–12 across selected schools and colleges. Quantitative data were gathered through structured questionnaires, supplemented by qualitative insights from semi-structured interviews, focus group discussions, and document analysis. Results indicate that 59.6% of respondents used tobacco in some form, with the highest prevalence among the 14–16 age group. Contrary to common perceptions, tobacco use was more prevalent among females than males, and usage rates were higher among college students than school students. Nearly 70% of respondents came from joint families, and a significant proportion belonged to agricultural households, some engaged in tobacco cultivation. Family tobacco use, peer pressure, and media exposure emerged as strong predictors of adolescent tobacco consumption. Despite widespread awareness of tobacco’s health risks, social acceptance and inadequate enforcement of existing policies perpetuate high usage rates. The findings highlight an urgent need for comprehensive, multi-level interventions that address familial and community influences, regulate media portrayals, and strengthen policy implementation within educational settings.